Kinetics of diesel degradation by an acrylamide-degrading bacterium - Ahmad, Siti Aqlima; Ku Ahamad, Ku Nurul Ezreen; Wan Johari, Wan Lutfi; Halmi, Mohd Izuan Effendi; Abd. Shukor, Mohd Yunus; Yusof, Mohd Termizi (Springer Milan, 2014)
In this work, we characterized a novel acrylamide-degrading bacterium with the ability to degrade diesel. Tentatively, the isolate was identified as Burkholderia sp. strain DRY27 and was shown to have increased growth rate on media supplemented with 0–3 % (v/v) diesel. We showed that sodium nitrate is the best nitrogen source for the bacterium growth on diesel. The optimal temperature and optimal pH supporting growth on diesel were between 10 and 40 °C and pH 7.5–8.5, respectively. Growth kinetics modeling showed that the Haldane model gave a correlation coefficient value of 0.99 and was better than other kinetic models such as Luong or Monod. Using the Haldane model, the maximum growth rate (µ max) was 0.305 h−1, while the saturation constant or half-velocity constant K s and inhibition constant K i, were 1.171 % (v/v) or 9.95 g/L and 3.215 % (v/v) or 27.32 g/L diesel, respectively. Microbial adhesion to hydrocarbon assay showed that after extraction, 65 % of the bacterium was found in the hexadecane phase indicating that the bacterium was hydrophobic. We showed that diesel components were completely removed based on the reduction in the hydrocarbon peaks monitored by solid-phase microextraction gas chromatography analysis.